CORRELATION BETWEEN SCREEN TIME AND VISUAL ACUITY DETERIORATION IN ADOLESCENTS: A CROSS-SECTIONAL STUDY - Dr. Ashish Sanjay Sarode, Dr. Ankur Anil Jhavar, Dr. Rahul Vasudeo Jawale, Dr. Dilip Onkar Patil, Dr. Dinesh Eknath Nehete, Dr. Chetan Bhagwat Chaudhari (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The rapid increase in screen usage among adolescents has raised concerns aboutpotential negative effects on visual health. This study explores the correlation between screentime and visual acuity deterioration among adolescents, providing insights into an issue of growing public health importance.